Numerical Solution of Fractional Diffusion-Wave Equation. (2nd January 2016) - Chen, An; Li, Changpin
ABSTRACT: In this article, a novel compact finite difference scheme is \mboxconstructed to solve the fractional diffusion-wave equation based on its equivalent integro-differential equation. In the temporal direction, the product trapezoidal scheme is employed to treat the fractional integral term. The convergence and stability of the scheme are proved. Numerical examples are also provided to verify the theoretical analysis.